Emerging drugs for non-alcoholic steatohepatitis. (September 2013) - Tomeno, Wataru; Yoneda, Masato; Imajo, Kento; Ogawa, Yuji; Kessoku, Takaomi; Saito, Satoru; Eguchi, Yuichiro; Nakajima, Atsushi
Abstract : Introduction: The prevalence of non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) is increasing along with the worldwide epidemic of obesity and their strong association with metabolic syndrome. Currently existing pharmacological therapies include anti-oxidants, insulin-sensitizing agents, lipid-lowering drugs and cytoprotective agents, but there is a lack of consensus regarding the most effective and appropriate pharmacologic therapies for NASH. Clinical trials examining new therapeutic drugs for NASH that act via various mechanisms are being performed in several countries, and these drugs may strongly influence current NASH treatment. Areas covered: This article provides a review of recent data on the safety and efficacy of existing and emerging agents for the treatment of NASH. Expert opinion: Ideally, treatment for NASH should not only improve liver disease, but also reduce the risks of adverse cardiovascular outcomes and the development of diabetes and cancers. However, this goal is likely to be too high in the context of clinical trials designed to obtain approval for the treatment of liver disease. The only way to achieve the goal is to accumulate the results of these relatively short-term clinical trials.